2019
DOI: 10.1259/bjr.20190184
|View full text |Cite
|
Sign up to set email alerts
|

Spect perfusion imaging versus CT for predicting radiation injury to normal lung in lung cancer patients

Abstract: Objectives: In non-small cell lung cancer (NSCLC) patients, to establish whether the fractional volumes of irradiated anatomic or perfused lung differed between those with and without deteriorating lung function or radiation associated lung injury (RALI). Methods: 48 patients undergoing radical radiotherapy for NSCLC had a radiotherapy-planning CT scan and single photon emission CT lung perfusion imaging (99mTc-labelled macroaggregate albumin). CT defined the anatomic and the single photon emission CT scan (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…SPECT ( x,y,z ) ' is the processed SPECT value. HIR is the high-intensity region value, which was set as the 75 th percentile of the pixel values in this study since this is close to the normal lung perfusion ( 25 ). discretize indicates the above described SPECT discretization.…”
Section: Methodsmentioning
confidence: 99%
“…SPECT ( x,y,z ) ' is the processed SPECT value. HIR is the high-intensity region value, which was set as the 75 th percentile of the pixel values in this study since this is close to the normal lung perfusion ( 25 ). discretize indicates the above described SPECT discretization.…”
Section: Methodsmentioning
confidence: 99%
“…The signal intensity of a lung SPECT image is strongly affected by the patient's condition, such as the respiratory capacity, frequency, diseases, etc. To ensure the perfusion value is comparable between patients, the SPECT perfusion was normalized to the 75th percentile value for each image, as this is close to the perfusion value of normal-functioning lung tissue (25). The CT-based perfusion images were then compared with the SPECT perfusion images via multi-level evaluations, including voxel-wise correlation, function-wise similarity, and lobe-wise agreement.…”
Section: Transfer Learning Framework For the Generation Of Ct-based P...mentioning
confidence: 99%
“…Q SPECT is performed with 99m Tc-MAA [77][78][79]. Studies have shown that local changes in Q scans correlate with radiation-induced lung damage from EBRT [80][81][82][83][84], and have noted the value of pre-treatment Q scans in the radiotherapy planning and the prediction of lung injury [85][86][87][88], with efforts made to also incorporate V scan data [89]. Recently, with the advent of V/Q PET, using 6 8 Ga-tagged Fig.…”
Section: Lungsmentioning
confidence: 99%